Structural characteristics and chloride intrusion mechanism of passive film. (October 2022) - Xu, Longjun; Wu, Pangang; Zhu, Xingji; Zhao, Guochen; Ren, Xiulian; Wei, Qifeng; Xie, Lili
Abstract: Passive film is a natural barrier against corrosion, which forms spontaneously in alkaline solution. But as a key problem for corrosion resistance, the growth and failure process of passive film has not been clearly confirmed. In this paper, the fine structure of passive film is explored on the atomic scale, and the growth mode of crystals is demonstrated; ion channels are found in inner passive film, which explains the appearance of defect zones and concentrated attack of chloride ions in corrosion. This study will help to judge the corrosion initiation from the perspective of micro damage of passive film. Highlights: A fine 5-layer structure of passive film in the growth process was found. Crystal growth and amorphous aggregation is promoted by chloride ions in short term. Putting forward special ion channel is the way that chloride invade the passive film.